Development of a mathematical model for the process of modernization of a melon cleaning machine - Kizatova, Marzhan; Baikenov, Alibek; Muslimov, Nurzhan; Baigenzhinov, Kadyrbek; Yessimova, Zhazira (Eastern-European Journal of Enterprise Technologies, 2021)
The paper is devoted to the problem of increasing the efficiency of melon processing under limited production automation. Measures for equipment modernization should be carried out in accordance with the operation rules of each individual unit. In production conditions, all equipment, without exception, undergoes this process, while the corresponding documentation is drawn up, confirming the implementation of modernization within a certain time frame. In a competitive market environment, product quality is a causal factor for the sharp increase in risks for food industry enterprises. To produce quality and competitive products, you need equipment that helps to reduce costs. The disadvantages of most melon peeling designs are size instability in the thickness of the rind. The paper presents a solution to this drawback. This was achieved by changing the sharpening angle of the rind cutting knife. Research has been carried out to study the texture properties of “Mirzachulskaya” and “Raduzhnaya” melons. And also experiments on melon peeling based on the planning matrix of mathematical modeling. Based on the experiments, a model of the peeling process was constructed. The key factors to limit peeling waste were optimized. Calculations of the optimized parameters yielded the cutting knife sharpening angle of 40 degrees, a roller gap of 9 mm, as well as an average force applied of 1,375 N∙m. The data obtained can be used as a basis for the modernization of this machine for other melon varieties